Social Support, Spiritual Well-Being, and Quality of Life Among MSM and Transgender Women Living with HIV in Rural Thailand - Vongtree, Anongluk; Khumsaen, Natawan; Sungsakul, Wimonpan; Peawnalaw, Supannee; Chenchob, Panarat; Namwong, Tassamon (National Journal of Community Medicine, 2025)
Background: HIV/AIDS continues to be a significant public health challenge in Thailand, affecting not only the physical health but also the overall quality of life (QOL) of those living with the virus. Understanding the factors influencing QOL is crucial for developing effective interventions and support systems. This study examined the QOL among men who have sex with men (MSM) and transgender women (TGW) living with HIV in Thailand and identify factors that are associated with their QOL. Methods: A cross-sectional quantitative design with secondary analysis was employed. Standardized measures were used to assess social support, spiritual well-being (SWB), and QOL. Data were analyzed using descriptive statistics and Pearson’s correlation coefficient. Results: Social support was found to be at a moderate level, while SWB was high. Overall QOL was moderate. QOL scores were significantly higher among those with a bachelor’s degree, those earning 20,001-30,000 baht monthly, and those who had disclosed their HIV status (p<0.05). Significant positive correlations were observed between QOL and both social support (r=0.459, p<0.05) and SWB (r=0.501, p<0.05). Conclusion: The findings revealed that moderate level of overall social support and high level of overall SWB significantly influence QOL among MSM and TGW. These findings provide a foundation for developing targeted nursing interventions that focus on social support and SWB to improve QOL among MSM and TGW.